2017
DOI: 10.1111/geb.12692
|View full text |Cite
|
Sign up to set email alerts
|

Climate contributes to the evolution of pesticide resistance

Abstract: Aim The evolution of pesticide resistance through space and time is of great economic significance to modern agricultural production systems, and consequently, is often well documented. It can thus be used to dissect the evolutionary and ecological processes that underpin large‐scale evolutionary responses. There are now nearly 600 documented cases of pesticide resistance in arthropod pests. Although the evolution of resistance is often attributed to the persistent use of chemicals for pest suppression, the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 54 publications
(79 reference statements)
4
39
0
Order By: Relevance
“…It would also be interesting to revisit the previous sample sites of a large comprehensive study involving D. melanogaster and repeat the experiments in a few decades to determine whether climate change has affected the allele frequency of these populations over time. Another method is to use long‐term climatic data and insecticide usage records to build models that may predict how these two variables interact in the development of field resistance, as discussed in the introduction …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would also be interesting to revisit the previous sample sites of a large comprehensive study involving D. melanogaster and repeat the experiments in a few decades to determine whether climate change has affected the allele frequency of these populations over time. Another method is to use long‐term climatic data and insecticide usage records to build models that may predict how these two variables interact in the development of field resistance, as discussed in the introduction …”
Section: Discussionmentioning
confidence: 99%
“…Evidence that climate can influence the evolution of resistance in the field is supported by modeling the association between long‐term climatic data and insecticide usage or resistance data in specific regions. An analysis of pyrethroid resistance in the redlegged earth mite, Halotydeus destructor , a major pest of Australia's grain and pastoral industries, across many regions in Western Australia indicated that regional variations in aridity, temperature seasonality, and precipitation patterns affected the spatial pattern of resistance . Another study modeling the development of deltamethrin resistance in Triatoma infestans , a Chagas disease vector, suggests that climate may influence the development of resistance in a region in Argentina …”
Section: Climate Change and Insecticide Resistancementioning
confidence: 99%
“…A technique commonly applied in machine learning was recently used to successfully capture the current distribution of insecticide resistance of H. destructor within Australia from environmental and management factors hypothesized to increase resistance risk. This modeling highlighted geographic locations without resistance, but with similar properties to areas with resistance . Since this study, resistant field populations have been detected within regions identified as high risk (Fig.…”
Section: The Future Of Resistance Management In Australian Grainsmentioning
confidence: 75%
“…Both help to bring additional value to the monitoring and management programs described earlier (Table ). For example, models can aid in identifying high‐risk areas or practices for pre‐emptive management . The evolution and management of insecticide resistance is multi‐dimensional, and computational approaches help in making this complexity more manageable and in identifying factors influencing resistance risk …”
Section: The Future Of Resistance Management In Australian Grainsmentioning
confidence: 99%
“…Few growers implement practices that mitigate the impact of insecticides on natural enemies (Roubos et al 2014). Given that there are only four mode-of-action pesticide groups in products registered to control H. destructor and that resistance against two has been demonstrated, the long-term viability of pesticide-based control options is uncertain (Maino et al 2018). However, grain growers will face new challenges in the future that may alter how and when they use insecticides.…”
Section: Introductionmentioning
confidence: 99%